A randomized controlled trial of technology‐enhanced behavioral parent training: sustained parent skill use and child outcomes at follow‐up. (9th December 2021) - Parent, Justin; Anton, Margaret T.; Loiselle, Raelyn; Highlander, April; Breslend, Nicole; Forehand, Rex; Hare, Megan; Youngstrom, Jennifer K.; Jones, Deborah J.
Abstract : Background: Early‐onset (3–8 years old) disruptive behavior disorders (DBDs) have been linked to a range of psychosocial sequelae in adolescence and beyond, including delinquency, depression, and substance use. Given that low‐income families are overrepresented in statistics on early‐onset DBDs, prevention and early‐intervention targeting this population is a public health imperative. The efficacy of Behavioral Parent Training (BPT) programs such as Helping the Noncompliant Child (HNC) has been called robust; however, given the additional societal and structural barriers faced by low‐income families, family engagement and retention barriers can cause effects to wane with time. This study extends preliminary work by examining the potential for a Technology‐Enhanced HNC (TE‐HNC) program to improve and sustain parent skill proficiency and child outcomes among low‐income families. Methods: A randomized controlled trial with two parallel arms was the design for this study. A total of 101 children (3–8‐years‐old) with clinically significant problem behaviors from low‐income households were randomized to HNC ( n  = 54) or TE‐HNC ( n  = 47). Participants were assessed at pre‐treatment, post‐treatment, 3‐month, and 6‐month follow‐ups. Primary outcomes were parent‐reported and observed child behavior problems. Secondary outcomes included observed parenting skills use (ClinicalTrials.gov Identifier: NCT02191956). Results: Primary analyses used latent curve modeling to examine treatment differences in the trajectory of change during treatment, maintenance of treatment gains, and levels of outcomes at the 6‐month follow‐up. Both programs yielded improvements in parenting skills and child problems at post‐treatment. However, TE‐HNC families evidenced greater maintenance of parent‐reported and observed child behavior and observed positive parenting skills at the 6‐month follow‐up. Conclusions: Our findings contribute to an ongoing line of work suggesting that technology‐enhanced treatment models hold promise for increasing markers of engagement in BPT and sustaining long‐term outcomes among low‐income families.